Pita Maha Social-Institutional Capital (A Social Practice on Balinese Painters in 1930s) - I Wayan Adnyana (Graduate School of Institut Seni Indonesia Yogyakarta, 2015)
Research Topic: Pita Maha Social-Institutional Capital (A Social Practice on Balinese Painters in 1930s) aims at describing creative waves of Balinese village youth in designing new paintings. The artwork is considered to be the latest development of classical paintings of Kamasan puppet. The pattern of development is not just on artistic technique, but also on aesthetic paradigm. Yet, the invention and development of painting concept, which were previously adopted from stylistic pattern of puppet Kamasan has successfully disseminated paintings as a medium of personal expression. The artist and patron consolidated art practice in the art function, which was well ordered and professional. Agents including palaces, Balinese and foreign painters as well as collectors and dealers were united in arts social movement, named Pita Maha. Despite the fact that Pita Maha also encompassed the sculpture, this research focuses more on the path of paintings. Socio-historical method is applied to explore the characteristics and models of social capital-institutional ideology that brought forth and commercialized paintings on Pita Maha generation. This topic is also an important part of the writer’s dissertation entitled Pita Maha: Social Movement on Balinese Paintings in 1930s. The discussion on socialinstitutional capital enables expansion and exploration of a more complete socio-historical construction on Pita Maha existence. The study on social capital aspects, which embodies the initiation of Pita Maha, has constructed a tremendous growth of Balinese paintings, both in terms of aesthetic “ideology”, and institutional competence of the painters.